6(1+3m)=8(-2m+5)-4

Simple and best practice solution for 6(1+3m)=8(-2m+5)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1+3m)=8(-2m+5)-4 equation:


Simplifying
6(1 + 3m) = 8(-2m + 5) + -4
(1 * 6 + 3m * 6) = 8(-2m + 5) + -4
(6 + 18m) = 8(-2m + 5) + -4

Reorder the terms:
6 + 18m = 8(5 + -2m) + -4
6 + 18m = (5 * 8 + -2m * 8) + -4
6 + 18m = (40 + -16m) + -4

Reorder the terms:
6 + 18m = 40 + -4 + -16m

Combine like terms: 40 + -4 = 36
6 + 18m = 36 + -16m

Solving
6 + 18m = 36 + -16m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '16m' to each side of the equation.
6 + 18m + 16m = 36 + -16m + 16m

Combine like terms: 18m + 16m = 34m
6 + 34m = 36 + -16m + 16m

Combine like terms: -16m + 16m = 0
6 + 34m = 36 + 0
6 + 34m = 36

Add '-6' to each side of the equation.
6 + -6 + 34m = 36 + -6

Combine like terms: 6 + -6 = 0
0 + 34m = 36 + -6
34m = 36 + -6

Combine like terms: 36 + -6 = 30
34m = 30

Divide each side by '34'.
m = 0.8823529412

Simplifying
m = 0.8823529412

See similar equations:

| 2.00x-15.00=25.00 | | 3x+y=73 | | 11y-4=9y | | -5(y+7)=7-4y | | 4X+56=8X | | 6a+5=16 | | -15.00+2.00x=-11.00 | | 3ax^3+3ay= | | r=2s-8 | | 2x^3+3x-2x-3=0 | | x^3-4x+x^2-4= | | 21-6x=2x+1 | | a^3-3a^2-28a= | | 5x+3x(2x+5)=180 | | 2a^3-2= | | 3(45+6)-45=2(45+3)-7 | | 2a^2x-4abx+2b^2x= | | 0.7(x+10)+0.9x=71 | | -101=7+9x | | 2x-32=1 | | 3x^2-3x-6= | | 8x+(-3)=-67 | | 3x+2=2.5 | | 7=2x-10 | | 4x+(5x+1)=10 | | 3ax^2-3a= | | C+CMP= | | -(6y+5)-(-5y-8)=2 | | 12(3x+3)-7(2x-2)=12x-10 | | 8(u-7)+6=-34 | | 20x-3=40x+5 | | 5x-4x+2x+3x-7= |

Equations solver categories